Annual energy performance of a thermoelectric heat pump combined with a heat recovery unit to HVAC one passive house dwelling. (5th March 2022) - Díaz de Garayo, S.; Martínez, A.; Astrain, D.
Highlights: TeHP technology provides appropriate HVAC for Passive House dwellings. It provides comfort conditions and precise temperature control with 15.3 kWh/m 2 y. Estimated TeHP COP ranges between 1 and 2 for heating and 0.5–1.7 for cooling. This consumption can be produced with 1 kWp PV (4 panels) for a 74 m 2 dwelling. Vapor compression technology saves 36.1% of the energy. This represents the reduction of 270 Wp (1 or 2 PV panels) per dwelling. Abstract: This paper proposes a HVAC system that integrates a thermoelectric heat pump with a double flux ventilation system and a sensible heat recovery unit able to provide heating, cooling and ventilation to a 74.3 m 2 Passive House certified dwelling in Pamplona (Spain). This study computationally investigates the energy performance of the system and the comfort conditions of the dwelling for one year long. The thermoelectric HVAC system maintains adequate comfort conditions with an indoor temperature between 20–23 °C in wintertime and 23–25 °C during summer, thanks to the precise control of the voltage supplied to the thermoelectric heat pump that can regulate the heating/cooling capacity from 5 to 100 %. The system consumes 1143.3 kWh/y (15.3 kWh/m 2 y) of electric energy, that can be provided by 4 photovoltaic panels of 250 Wp each. This system is then compared with a vapor compression heat pump with a COP of 4.5. The vapor compression system reduces the electric energy consumption by 36.1 % with respect to the thermoelectric system, which allows saving only 270 Wp (1–2 PV panels). This demonstrates the promising application of thermoelectricity for HVAC in passive houses.